(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
Before the development of subaltern historiography, history was always an elite pursuit. Subaltern historiography has played an important role in de-elitising history and bringing forth the facts of socio-economic aspects and political events during the colonial period. In colonial Orissa, there were numerous subaltern movements in general, and tribal insurgencies in particular, all aiming for some or other form of independence from the clutch of landed aristocracy, local rajas, or the British. Tribals played a significant political role in Orissa’s freedom struggle in 19th and 20th centuries. They were not at all backward in colonial Orissa’s prajamandal movements. But it is a farce that, even after a long interval, just a few tribal leaders have gained prominence in history, which shows a gap in political history and a grave intellectual injustice. Colonial historiography portrayed tribals as criminals and blind-believers with negative activities. But the influence of Marxist and Subaltern approach has changed the historiographical scenario in the post-independent phase, which is evidenced from the extensive studies on socio-economic and cultural life of the tribals. Despite extensive studies, political history of tribals has received less attention in comparison to socio-economic history. Similarly, the history of science and technological knowledge in proverbs, health care practices, animal husbandry have not yet explored. Travesty, we are obliged to rely exclusively on inadequate colonial documents, which appear to be biased, due to a lack of indigenous records. As a result, the need of oral source, vernacular sources and artefacts preserved in museums are felt significantly. Intensive research within the conceptual framework of an interdisciplinary approach is also required to learn more about their other aspects of life and for bringing an intellectual justice.